Large Animal Emergency Relief Services—A Model for University Engagement With Private Practitioners and Development of Practice Readiness for Veterinary Students - Graves, Meggan T.; Anderson, David E.; DeNovo, Robert C. (Frontiers in Veterinary Science, 2020)
Large animal teaching hospitals often struggle to maintain consistent teaching caseloads, which are affected by seasonal variations, economic pressures, increased abilities of local large animal practices to hospitalize large animals, and client intolerance for the operational needs of an academic mission. Non-academic large animal practices enjoy a more consistent caseload but suffer from a lack of emergency relief and a limited ability to share emergency duties, which may have adverse effects on work-life balance. An academic, on-farm, large animal emergency relief service can combine multiple clinics’ emergency services to increase overall caseload and the probability of consistent teaching exposure for veterinary students. In late November of 2013, the Large Animal Teaching Hospital at the University of Tennessee, College of Veterinary Medicine adopted a business model to provide a large animal emergency relief service to area practitioners; enhance student learning via increased emergency caseload; and advance the academic mission to develop practice-ready graduates. Providing this service contributes to the well-being of area practitioners and enriches student learning through increased caseload.